A stronger union through crisis? 25 years of monetary integration in Europe - Ferdinand Fichtner; Philipp König (DIW Economic Bulletin, 2015)
On July 1, 1990, when capital controls in the European Economic Community were removed, the path was paved for the introduction of the euro. This path was marked by a compromise between two schools of thought-those who assumed that the creation of the European Central Bank would be followed by greater economic convergence and political integration, and those who saw the single currency as the coronation of European cooperation and economic convergence. In the initial years following the introduction of the single currency, the compromise as set down in the Maastricht Treaty-the speedy introduction of the single currency, on the one hand, and better cooperation in fiscal policy matters on the other-neither strengthened the institutional foundations of the monetary union nor advanced the political integration process. This resulted in economic divergence and tension in the euro area, which in recent years culminated in a severe crisis. It was only in response to this crisis that some of the necessary changes to the institutional structures of the monetary union were made. There is much evidence to suggest that, when the monetary union was originally being created, such tension and even crisis situations were consciously tolerated because of the stimulus for deeper integration this would provide. Such political maneuvering is very risky, however, since it can lead to the loss of public support for the integration process, thereby threatening the very existence of the common currency. To advance the European project, it is imperative that governments do not rely on the momentum inherent in crisis situations, but instead press ahead with the next stages of integration and take an active approach to bolstering the institutional foundations of the currency union.
Keywords: E42; F15; F33; F45; N14; 330; monetary integration; crises; institutions; European Monetary Union; economic integration; capital movements